ASSESSMENT FOR WRITING SKILLS IN ONLINE LEARNING - Dwiyanti, Kadek Erlita; Suwastini, Ni Komang Arie (Universitas Pendidikan Ganesha, 2021)
Covid-19 pandemic required learning to be done online. Likewise, the assessment had to be done online. This study intended to examine the assessment of writing skills on online learning in Senior High School (SMA) in Denpasar. The study was a qualitative approach with a structured interview. Eight questions were asked to an English teacher to explore how the writing assessment in online learning done by the teacher. The findings showed that the teacher already understood the importance of assessment and already done the authentic assessment, formative assessment, and summative assessment. However, in assessing the writing, several aspects such as the organization of the writing, discourse, and mechanics (punctuation, spelling, and capitalization) were not assessed by the teacher. Additionally, the teacher faced some obstacles in terms of plagiarism/originality of students’ writing and time management in conducting writing assessments on online learning. To solve this problem, the teacher warned the students about plagiarism and used an online plagiarism checker to check the authenticity of student work. Furthermore, to solve the problem of time-management teachers divided the time strictly between planning, teaching, and assessing. The research suggested that there is a need to conduct training for teachers to do online assessment,s especially on writing skills.